2021
DOI: 10.1186/s13099-021-00410-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the virulence genes and the biofilm formation associated operons in Vibrio parahaemolyticus

Abstract: Background The membrane fusion protein (mfp) gene locus of Vibrio parahaemolyticus consists of two operons, cpsQ-mfpABC and mfpABC, which are both required for biofilm formation. ToxR and CalR are required for the full virulence of V. parahaemolyticus, and their mutual regulation has been demonstrated. Moreover, cell density-dependent expression of toxR was previously observed in V. parahaemolyticus, but details about the related mechanisms remained unclear. QsvR can work with the master quorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In the present work, the results of qRT-PCR displayed that most T3SS1-related genes were downregulated in Δ vmeL compared with wild type strains. A similar study found that RND null mutants increased leuO transcription in V. cholera ( Bina et al, 2018 ), and the leuO -homologous protein CalR repressed the transcription of T3SS1 in V. parahaemolyticus ( Gode-Potratz et al, 2010 ; Zhang et al, 2021b ). Therefore, we inferred that VmeL mediates cytotoxicity by indirectly modulating the transcription of T3SS1 by an unknown mechanism.…”
Section: Discussionmentioning
confidence: 72%
“…In the present work, the results of qRT-PCR displayed that most T3SS1-related genes were downregulated in Δ vmeL compared with wild type strains. A similar study found that RND null mutants increased leuO transcription in V. cholera ( Bina et al, 2018 ), and the leuO -homologous protein CalR repressed the transcription of T3SS1 in V. parahaemolyticus ( Gode-Potratz et al, 2010 ; Zhang et al, 2021b ). Therefore, we inferred that VmeL mediates cytotoxicity by indirectly modulating the transcription of T3SS1 by an unknown mechanism.…”
Section: Discussionmentioning
confidence: 72%
“…Our data showed that cpsQ and mfpABC were significantly induced and repressed in the wrinkly phenotype, respectively (Table S3). Considering that QsvR and AphA activate and repress the transcription of cpsQ-mfpABC and mfpABC , respectively ( 77 , 78 ), and both were induced in the wrinkly phenotype (Table S3), genes encoding Mfp proteins should be strictly regulated and balance changes in colony morphology.…”
Section: Resultsmentioning
confidence: 99%
“…This cyclic di-GMP is programmed by a capsular polysaccharide (CpsQ), which is part of the membrane fusion protein (MFP). The proteinencoding MFP locus is required for biofilm production in Vp (Zhang et al, 2021).…”
Section: Role Of Biofilm and Quorum Sensing Regulators For Adaptationsmentioning
confidence: 99%